Numerical and experimental examinations of free convection condensation of steam in the presence of air over the cooled panel - Koca, Aliihsan; Atayilmaz, S. Tzgr (ELSEVIER SCIENCE SA, 2022)
In this paper, experimental and numerical investigations have been conducted to evaluate the steam condensation in the presence of air over a vertical plate for a small temperature difference between the air and a cold wall. In the paper, we describe the experimental set-up, emphasizing the conditioning and measuring equipment introduced for this research. A numerical model is also described in detail. The estimated condensation quantities agreed well with the experimental data. According to the data, simulated total condensation quantities were higher than measured total condensation amounts in all cases, ranging from 6.8 to 13.4% (average 8.9%). The condensation rate increases by 28% as the sub-cooling temperature rises from 2.1 degrees C to 4.4 degrees C. The mass fraction of water vapor in the air also induces condensation. Average condensation flux decreases 41.7% when relative humidity decreases from 74.9 to 65.4% at the same surface temperature. In the last part, an empirical correlation, which is characterized by the partial pressure difference of water vapor at the surface and out of the boundary layer conditions, was proposed to estimate the condensation flux over the vertical plate. This practical correlation is novel and can be used for various engineering applications. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: Condensation; Radiant cooling; Free convection; Non-condensable gases; Steam condensation; HEAT-TRANSFER COEFFICIENTS; VERTICAL TUBE; GASES; FLOW; WALL; CFD; PERFORMANCE; CONTAINMENT; CONDENSERS; SYSTEMS; Construction & Building Technology; Energy & Fuels; Engineering